Adverse Effects of Statins - Myths and Reality - Simic, Iveta; Reiner, Zeljko (Current Pharmaceutical Design, 2015)
Statins reduce cardiovascular mortality and morbidity as well as cardiovascular events in patients with a very high risk of cardiovascular disease (CVD) and also in subjects with high or moderate risk by reducing the levels of low-density lipoprotein cholesterol (LDL-C). Although they are considered to be drugs with a very good safety profile, because of their wide use there are many concerns that their adverse effects might compromise their proven beneficial effects. Therefore this article reviews all the data and provides an evidence- based insight what are the proven adverse effects of statins and what are the “myths” about them. The most important side effects include myopathy and rhabdomyolysis. Another side effect is increased activity of liver tests which occurs occasionally and is reversible. However, recent studies even suggest that statin therapy can improve hepatic steatosis. It is beyond any doubt that statins do slightly increase the incidence of type 2 diabetes mellitus in people with two or more components of metabolic syndrome but the cardiovascular benefits of such a treatment by far exceed this risk. Statin therapy has also been associated with some adverse renal effects, eg. acute renal failure, but recent data suggest even a possible protective effect of these drugs on renal dysfunction. Concerns that statins might increase cancer have not been proven. On the contrary, several studies have indicated a possible benefit of these drugs in patients with different types of cancer. Early concerns about cognitive dysfunction and memory loss associated with statins use could not be proven and most recent data even suggest a possible beneficial effect of statins in the prevention of dementia. Systematic reviews and clinical guidelines suggest that the cardiovascular benefits of statins by far out-weight non-cardiovascular harms in patients with cardiovascular risk.
Keywords: dementia